Home management techniques and relationship of college roommates living in condominiums - Manapil, Alyanna R.; Sarmiento, Ana Rafaela L. (College of Home Economics, University of the Philippines Diliman, 2019)
This study describes the connection of the quality of friendship between college roomates to the home management techniques they employ to address challenges encountered and what factors influence the techniques employed. Fifteen pairs from Metro Manila were selected for face-to-face interviews where they also answered the McGill Friendship Questionnaire-Friendship Functions. Scores from the questionnaire were averaged to measure their friendship satisfaction. From the data gathered, five themes for the challenges encountered were identified, namely adjustment to condominium living, task accomplishment and delegation, roommate relationships, space and materials, and resources. Also identified were five categories for the techniques employed: task management, space management, relationship management, selfmanagement, and resource management. Eight factors that influence the home management techniques employed were also identified, namely personality and personal preference, family or home, availability and convenience, space, furniture, and materials, budget, culture, previous experience, and gender. It was found that it is important for roommates to have a good relationship so that they can function efficiently. It was recommended that institutions create programs to help college roommates adjust to challenges encountered. Families are encouraged to find the balance with regard to their child's independence. Lastly, college roommates are encouraged to have open communication for a better household.